ANALISIS EFISIENSI PRODUKSI DAN PENDAPATAN USAHATANI JAHE DI KECAMATAN PENENGAHAN KABUPATEN LAMPUNG SELATAN - Riki Misgiantoro; Fembriarti Erry Prasmatiwi; Indah Nurmayasari (Lampung University, 2017)
This research aims to analyze the production efficiency of ginger farming, factors affecting technical efficiency of ginger farming, and income of ginger farming in Penengahan Subdistrict of South Lampung Regency. This research uses a survey method and the location was chosen purposively at Way Kalam Village, Penengahan Subdistrict of South Lampung Regency with consideration that the location is the central of ginger production. The samples were 83 ginger farmers who were selected randomly. Data were collected in April – Mei 2016 and were analyzed using descriptive and quantitative analyses, namely frontier production function, multiple linear regression, and income analysis. The results showed that ginger farming in Penengahan Subdistrict of South Lampung Regency was not technically efficient because the efficiency has only reached 63%. The factors that influence significantly in technical efficiency of ginger farming were scale farming, cost, revenue, and risk. Ginger farming in Penengahan Subdistrict South Lampung Regency was a profitable farming with the R/C value of 1.51 and income of Rp21,405,070.20 per hectar. Key words: frontier production function, ginger farming, technical efficiency